Existence of Solutions for the Semilinear Abstract Cauchy Problem of Fractional Order - Henriquez-Miranda, H (De Gruyter Open Ltd, 2021)
In this paper we establish the existence of solutions for the nonlinear abstract Cauchy problem of order α (1, 2), where the fractional derivative is considered in the sense of Caputo. The autonomous and nonautonomous cases are studied. We assume the existence of an α-resolvent family for the homogeneous linear problem. By using this α-resolvent family and appropriate conditions on the forcing function, we study the existence of classical solutions of the nonhomogeneus semilinear problem. The non-autonomous problem is discussed as a perturbation of the autonomous case. We establish a variation of the constants formula for the nonautonomous and nonhomogeneous equation. © 2021 Diogenes Co., Sofia.